Psychometric properties of patient-reported outcome measures of self-management for cancer survivors: a systematic review protocol using COSMIN methodology - Yan Hu; Zheng Zhu; Weijie Xing; Jian Peng; Yiting Chen; Lanjun Shen; Guodong Jin (BMJ Open)
Introduction Self-management is an important strategy for cancer survivors. Evaluating self-management is essential for planning nursing interventions that promote self-management and for measuring the contribution of nursing to health outcomes. Many patient-reported outcome measures (PROMs) have been designed and used to assess self-management in cancer survivors. However, it is unclear which PROM has the best reliability and validity. Therefore, the goal is to systematically review the psychometric properties of existing self-management PROMs and determine which PROM is best for cancer survivors.Methods and analysis This systematic review will be conducted according to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines for systematic reviews of PROMs. Ten electronic literature databases (PubMed, EMBASE and so on) and two websites for PROMs will be searched from inception to 1 March 2020. Studies testing the psychometric properties of PROMs assessing self-management for cancer survivors, published in either English or Chinese, will be included. Two independent reviewers determined the eligibility of the studies and will independently extract the data. Risk of bias will be assessed using the COSMIN risk-of-bias checklist, and the quality of the results will be assessed using specific COSMIN quality criteria.Ethics and dissemination It is not necessary to obtain ethical approval for this systematic review protocol. The results will be published in a peer-reviewed journal and presented at a relevant conference.PROSPERO registration number CRD42020149120.